P-796 Intraovarian injection of plasma rich in growth factors improves ovarian reserve and reproductive outcomes in women with diminished ovarian reserve. (30th June 2022) - Herraiz, S; Ruiz, P; Garrido, N; Ballester, A; Vergara, V; Cruz, M; Requena, A; García-Velasco, J A; Muñoz, M
Abstract: Study question: Does Plasma rich in growth factors (PRGF) ovarian injection increase the ovarian reserve biomarkers in women with diminished ovarian reserve? Summary answer: PRGF injection increased Antimüllerian hormone (AMH) levels and antral follicular count (AFC) since the first follow-up after treatment allowing the initiation of ovarian stimulation cycles. What is known already: Several techniques based on in vitro activation, ovarian fragmentation and stem cell ovarian transplantation have been proposed to reactivate ovarian function and increase IVF success in women with premature ovarian insufficiency and poor ovarian response. However, less invasive and feasible approaches are still required for those patients where egg donation is the only practical option. Platelet rich plasma (PRP) and PRGF contain a high concentration of platelets, which carry more than 800 types of proteins, cytokines, hormones, and chemoattractants. Indeed, intraovarian PRP injection has recently been used in different case series and cohort studies of POI women with encouraging results. Study design, size, duration: Retrospective study with 104 women aging 23-45 years who received a PRGF intraovarian injection (REGENERA-Ovario) was conducted between 2020 and 2021 at IVIRMA Alicante (Spain). Study was approved by the IRB committee of La Fe University Hospital (2112-FIVI-109-SH). Participants/materials, setting, methods: Patients underwent a PRGF injection (Endoret kit; B.T.I. Biotechnology Institute S.L, Spain) in both ovaries and a follow up of ovarian reserve biomarkers (AFC, AMH) and follicle stimulating hormone (FSH) to evaluate follicular reactivation seeking IVF or spontaneous pregnancy. The follow up visits ranged from 1 to 5 months and were developed on a monthly basis after treatment or after menses recovery in POI. Study variables were compared to basal levels with a paired t-test. Main results and the role of chance: Overall, 104 women (age: 38.7±2.0 years; BMI: 22.1±2.9) with diminished ovarian reserves underwent a PRGF intraovarian injection (3.3±0.8ml PRGF/each ovary). Prior to treatment, our cohort was characterized high serum FSH (21.8±4.1mIU/mL), low AMH levels (0.25±0.37ng/ml), and an ovarian volume of 6.3±2.3cm 3 . Eighty-eight of them fulfilled the 1 st follow up visit and showed an increase of serum AMH (0.25±0.37ng/ml vs. 0.32±0.36ng/ml, p = 0.008), and AFC in both ovaries (2.1±1.9 vs. 3.2±2.4, p < 0.0001) compared to basal levels, achieving ovarian reactivation in 55.9% of them and IVF cycle initiation in 19.3%. These improvements were higher 2 months after treatment (55 patients), with increased antral follicles (AFC-2: 2.9±2.5, p = 0.0001) and ovarian activation in 58.2%, and IVF start in 43.9% of patients. Similar results were observed during the 3 rd follow up accomplished by 30 women and lasted until the 5 th visit (n = 8), although the reduced patient number at this point. A total of 44 IVF cycles were started and oocyte pick-up was successfully developed in 72.7% of them with a mean number of 3.3±4.2MII oocytes, 1.8±2.1 fertilized oocytes and 1.5±2.0 embryos per cycle. Indeed, 6 pregnancies were obtained during this period, 2 of them after embryo transfer and 4 by natural conception. Limitations, reasons for caution: Our results are encouraging but a large cohort of patients with a longer follow up period is needed to establish the efficacy and duration of the PRGF positive ovarian effects. Moreover, a proper comparison with a control group with the same characteristics and no PRGF intervention is still required. Wider implications of the findings: PRGF intraovarian injection reactivates follicle growth and allows IVF cycle initiation and embryo generation in a poor prognosis population of patients with diminished ovarian reserve. The effects persisted for several months after treatment. Trial registration number: 2112-FIVI-109-SH